The application of Dynamic Programming in the Ebonyi State Building Materials Industry Ezzamgbo, Nigeria - Okpara, Patrick Agwu; Aloke, Sunday Nwokpoku; Majindu, Nnaemeka; Ezeike, Nelson Nnamdi; Egwu, Egwu Ogbonnia; Abel, Okike (Budapest International Research in Exact Sciences (BirEx) Journal, 2025)
This study examined how the dynamic programming technique was applied to the Ebonyi State Building Materials Industry in Ezzamgbo, Nigeria, in order to maximize profits. The study looked at how effective dynamic techniques are in the industry for making decisions. The Administration, Management, Statistical, and Research department of the industry provided the data for the study. Dynamic programming was utilized in this study to model the industry data that was gathered. Concrete blocks, electric poles, and culvert rings are among the three raw materials produced by the industry in a range of sizes. After the model was solved and applied to the industry, it was determined that, in order to maximize profit, the industry should only produce 10.3632-meter high tension electric poles for eight hours. According to the findings, the production of 32 sets of 10.3632-meter high tension electric poles using the entire 8-hour machine time allotted each day yielded the highest profit of N448,000